Strategic Disclosure of Intermediate Research Results. - Gill, D (Department of Economics (University of Oxford), 2004)
We analyze the incentives to disclose intermediate research results. We find that despite the help that disclosure can give to a rival, the leading innovator sometimes chooses to disclose. Disclosure signals commitment to the research project, which may induce a rival to exit. With weak product market competition, the leader discloses intermediate results that are sufficiently promising, while secrecy may be employed for very good results. As spillovers from disclosure increase, the leader becomes more secretive. With strong product market competition, the leader may rely entirely on secrecy but perhaps surprisingly invests more often at the intermediate stage.